2014
DOI: 10.1080/09585192.2014.891637
|View full text |Cite
|
Sign up to set email alerts
|

The interactive effects of leader–member exchange, gender and spouse's gender role orientation on work interference with family conflict

Abstract: Based on social support and gender role theories, we examined the direct and interactive effects of leader-member exchange, gender and spouse's gender role orientation on work-family conflict. Survey data were collected from matched dyads from 185 dual-earner couples in Sri Lanka. The results show that leader -member exchange is negatively related to work interference with family. There is also support for crossover effects among couples such that individuals with spouses who have a traditional gender role ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
64
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 64 publications
(80 reference statements)
2
64
0
1
Order By: Relevance
“…The top management started to believe that the high rate of turnover intention may be effectively mitigated by improving LMX relationship. In addition, very positive results may be observed with this social and occupational support (Kailasapathy, Kraimer, & Metz, 2014). This LMX relationship due to improved communications may also reduce role stressors and turnover intention and improve job satisfaction (Firth, Mellor, Moore, & Loquet, 2004;Zhang, Tsingan, & Zhang, 2013).…”
Section: Introductionmentioning
confidence: 87%
“…The top management started to believe that the high rate of turnover intention may be effectively mitigated by improving LMX relationship. In addition, very positive results may be observed with this social and occupational support (Kailasapathy, Kraimer, & Metz, 2014). This LMX relationship due to improved communications may also reduce role stressors and turnover intention and improve job satisfaction (Firth, Mellor, Moore, & Loquet, 2004;Zhang, Tsingan, & Zhang, 2013).…”
Section: Introductionmentioning
confidence: 87%
“…However, both must be interpreted with caution. Factors such as the relatively old publication date, the use of a student sample (Beutell & Greenhaus, ), the particular cultural context (Kailasapathy et al, ), and, importantly, the fact that both studies neglected the non‐independence of couple data in the analyses limit the interpretability of these findings, at least for the research question that the present study seeks to answer.…”
Section: The Impact Of Spouses' Gender‐role Attitudes On Working Mothmentioning
confidence: 99%
“…Beutell and Greenhaus () found that husbands' traditional gender‐role attitudes increased WFC of female students with children. A recent study with dual‐earner couples in Sri Lanka (Kailasapathy, Kraimer, & Metz, ) found that husbands' more traditional gender‐role attitudes were related to higher levels of WFC of their wives. Both studies lend initial empirical support to our contentions.…”
Section: The Impact Of Spouses' Gender‐role Attitudes On Working Mothmentioning
confidence: 99%
“…Along with these demographic shifts, employees are experiencing increased work‐life conflict as they struggle to balance their work and nonwork commitments (Allen, Herst, Bruck, & Sutton, ). In response to these trends, a growing number of organizations have invested in work‐life support (WLS) practices that provide employees with flexibility to help them to manage their various responsibilities (Kailasapathy, Kraimer, & Metz, ; Piszczek & Berg, ). While the attributes of WLS initiatives differ across firms, WLS practices often include flexible work schedules, teleworking, job sharing, working from home, leave of absence or gap leave, and dependent care programs (Butts et al, ).…”
Section: Introductionmentioning
confidence: 99%